Entrepreneurial Customers’ Decision for Purchasing Laundry Plastics Based on Product Quality, Price, Promotion and Distribution (Case Study: Jakarta, Tangerang and Bandung) - Respati Wulandari (Business Economic, Communication, and Social Sciences Journal (BECOSS), 2023)
This research is to determine the effect of Price, Product Quality, Distribution, and Promotion to Purchase Decision of Growth Packaging’s laundry plastic in Jakarta, Tangerang, and Bandung. We use quantitative methods and multiple regression analysis to get research finding. This research was conducted by distributing questionnaires to 55 respondents who are owners of laundry businesses in Jakarta, Tangerang, and Bandung. The findings of this study indicate that: Price and Distribution have a significant effect while Product Quality and Promotion have an unsignificant effect toward purchase of Growth Packaging’s laundry plastic in Jakarta, Tangerang, and Bandung.